Modern Ultrasound Methods of Studying the Biomechanical Properties of the Lens. Review - E. D. Sakalova; I. V. Andreeva; Y. M. Al-Mahdar (Oftalʹmologiâ, 2021)
Cataract is one of the most common diseases in ophthalmology nowadays, ranks first in the world among the causes of reversible blindness and remains a multifactorial disease, involving complex interactions between metabolic disorders, genetic predisposition and environmental risk factors. Studying the properties of the lens is important in “cataract” surgery from a clinical perspective. Determination of the mechanical hardness of the lens is particularly important to optimize the amount of ultrasonic energy expended during phacoemulsification in order to minimize the number of complications, however, the existing methods are rather subjective and based mainly on biomicroscopy with visual assessment. Ultrasound constitutes a significant part of the methods of studying the lens. There are methods for determining the density of the lens using A-scan (one-dimensional image) and B-scan (two-dimensional image). Basically, these techniques provide information on acoustic density, but not on mechanical hardness. Several studies have used a high frequency needle tranducer to determine the hardness of the lens. The authors believe that the combination of an ultrasound needle tranducer and a phacoemulcification probe for real-time feedback may provide better surgical efficiency. Ultrasound elastography, static and dynamic is used to assess the elastic properties of tissues in many areas of medicine. In ophthalmology, elastography is not used in general clinical practice, however, the density of the lens is assessed in vivo using compression elastography in some studies. Also, a number of researchers offer combined system of ultrasound elastography and OCT, called OCTelastography. It is assumed that OCT elastography can provide better spatial image resolution and faster acquisition rates. The literature review reveals summarized data on methods of studying the lens, its acoustic and mechanical density, using various ultrasound research techniques, including such poorly understood methods in ophthalmology as compression elastography and optical coherent elastography.